An investigation into the replicon of a broad host range mobilizable plasmid from the moderately thermophilic bacterium Acidithiobacillus caldus - Gardner, Murray Newell (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2003.